THE EFFECT OF LEARNING TECHNOLOGY, TRAINING MOTIVATION, AND TRAINING SATISFACTION ON TRAINING EFFECTIVENESS FOR EDUCATIONAL PERSONNEL AT MUHAMMADIYAH UNIVERSITY OF YOGYAKARTA: A MEDIATION TEST - Laela Niswatin; Meika Kurnia Puji Rahayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes the effect of learning technology on training effectiveness through the mediating role of training motivation and training satisfaction among educational staff at Universitas Muhammadiyah Yogyakarta. This research addresses the limited empirical studies regarding online training effectiveness in higher education administrative staff contexts. The study employed a quantitative explanatory approach using survey methods involving 126 respondents who participated in institutional online training programs from December 2025 to March 2026. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that learning technology significantly affects training effectiveness, training motivation, and training satisfaction. Furthermore, training motivation and training satisfaction significantly influence training effectiveness. Both variables also mediate the relationship between learning technology and training effectiveness. These findings highlight the importance of participant engagement and satisfaction in improving the success of online training programs.